Dispersion Analysis of Rounds Fired from a Glauberyt Machine Pistol - Zbigniew DZIOPA; Krzysztof ZDEB (Problemy Mechatroniki)
Within an enclosed shooting range of the EMJOT company, the process of firing one hundred single bullets from a Glauberyt machine pistol was recorded. The empirical test used 9x19 mm FMJ Luger (Parabellum) ammunition manufactured in the Czech Republic in 2017. As the weapon is dedicated to special forces, the shots were fired by an anti-terrorist operative, at a target located 25 m away. In order to determine bullet dispersion, the results of the experiment were subjected to statistical processing. Mean displacement and mean square displacement relative to the mean hit point, histograms, normal distribution, as well as statistical tests and hypotheses were used for estimation. The shots were recorded with a high speed digital camera Phantom v 9.1. The videos recorded were used to determine the initial kinematic parameters of the bullet trajectory.